1999
DOI: 10.1126/science.283.5399.212
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nonexercise Activity Thermogenesis in Resistance to Fat Gain in Humans

Abstract: Humans show considerable interindividual variation in susceptibility to weight gain in response to overeating. The physiological basis of this variation was investigated by measuring changes in energy storage and expenditure in 16 nonobese volunteers who were fed 1000 kilocalories per day in excess of weight-maintenance requirements for 8 weeks. Two-thirds of the increases in total daily energy expenditure was due to increased nonexercise activity thermogenesis (NEAT), which is associated with fidgeting, maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
685
8
17

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 874 publications
(733 citation statements)
references
References 19 publications
23
685
8
17
Order By: Relevance
“…Schoeller's overview emphasizes the relatively low amount of daily variation occurring in TEE and also the body's tendency to increase energy stores as the result of overfeeding. Levine et al (1999) emphasized the possibility of increased amounts of nonexercise activity thermogenesis (NEAT) to resist fat gain accompanied with overfeeding; however, it now appears that levels of NEAT are static within an individual, regardless of fat gain (Levine et al, 2005). To date, the effects of increased daily PA on TEE have produced conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Schoeller's overview emphasizes the relatively low amount of daily variation occurring in TEE and also the body's tendency to increase energy stores as the result of overfeeding. Levine et al (1999) emphasized the possibility of increased amounts of nonexercise activity thermogenesis (NEAT) to resist fat gain accompanied with overfeeding; however, it now appears that levels of NEAT are static within an individual, regardless of fat gain (Levine et al, 2005). To date, the effects of increased daily PA on TEE have produced conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Thermogenesis is an energy demanding process that has a significant contribution to daily 66 total energy expenditure (TEE), body weight and health (Levine, Eberhardt & Jensen 1999, 67 Rosenbaum et al 2008). High thermogenesis is linked to high physical activity (PA) level, as 68 body temperature rises as a result of increased muscular activity (Gleeson 1998).…”
Section: Voluntary Running Aids To Maintain High Thermo-genesis Inmentioning
confidence: 99%
“…15 It has been reported that low physical activity accounted for 77% of weight gain over a year in one prospective study 16 and inactivity is a major determinant of increased adiposity during overfeeding. 17 Indeed, the variability of response to an obesigenic environment may be explained by inter-individual differences in non-exercise physical activity, which vary over 30-fold. 3 An anti-obesity treatment which both increases activity and reduces energy intake is more likely to be a successful longterm therapy for obesity.…”
Section: Introductionmentioning
confidence: 99%